Agent Computing and Multi-Agent Systems 10th Pacific Rim International Conference on Multi-Agent Systems, PRIMA 2007, Bangkok, Thailand, November 21-23, 2007, Revised Papers - Ghose, Aditya; Governatori, Guido; Sadananda, Ramakoti (Lecture Notes in Artificial Intelligence, 2009)
This book constitutes the thoroughly refereed post-workshop proceedings of the 10th Pacific Rim International Workshop on Multi-Agents, PRIMA 2007, held in Bankok, Thailand, in November 2007. The 22 revised full papers and 16 revised short papers presented together with 11 application papers were carefully reviewed and selected from 102 submissions. Ranging from theoretical and methodological issues to various applications in different fields, the papers address many current subjects in multi-agent research and development,.